Synthesisi of zaO-NiO nanoparticle using solid-vapor phase thermar sublimation method - Ahmad Shuhadah bin Ismail, Ahmad Shuhadah (2009)
This report basically discusses the preliminary research done and basic understanding of the chosen topic, which is the "Synthesis of ZnO-NiO nanoparticle using solidvapor phase thermal sublimation method".